Sosialisasi Mengenai Pernikahan Dini Dalam Bidang Kesehatan Serta Aspek Hukum Pada Kelompok Remaja Di Kecamatan Deleng Pokhkisen Kabupaten Aceh Tenggara Tahun 2024 - Inneke Mutiara Amelia (Jurnal Pengabdian Ilmu Kesehatan, 2024)
Early marriage is a marriage that is not permitted because it violates the age limit for marriage, which stipulates that marriage must be done at the age of more than 20 years but is done when the age is under 20 years. Republic of Indonesia Law No. 1 of 1974 states that early marriage cannot be carried out if the bride and groom are underage. However, cases of early marriage in Indonesia always increase every year. Community Service Activities (PKM) Socialization regarding Early Marriage in the Health Sector and Legal Aspects among Youth Groups in Deleng Pokhkisen District, Southeast Aceh Regency in 2024 was held on March 2-3 2024 with a total of 45 participants. The extension participants seemed enthusiastic about the materials presented by the resource persons and were able to be actively involved, so that this extension activity took place in a two-way system and many participants asked questions. The presentation of the extension material was followed by discussion, ice breaking, and distribution of door prizes to participants who were active during the discussion activities.